Pickering emulsions stabilized by a lipophilic surfactant and hydrophilic platelike particles - Wang, Jun (Langmuir : the ACS journal of surfaces and colloids, 2010)
Liquid paraffin-water emulsions were prepared by homogenizing oil phases containing sorbitan oleate (Span 80) and aqueous phases containing layered double hydroxide (LDH) particles or Laponite particles. While water-in-oil (w/o) emulsions are obtained by combining LDH with Span 80, the emulsions stabilized by Laponite-Span 80 are always o/w types regardless of the Span 80 concentration. Laser-induced fluorescent confocal micrographs indicate that particles are absorbed on the emulsion surfaces, suggesting all the emulsions are stabilized by the particles. The difference of the particle-stabilized emulsion type may be explained by comparing particle contact angles and the oil-water interfacial tensions, indicating that more Span 80 molecules are adsorbed on the LDH particles than on Laponite. Apparently, the LDH particles are rendered more hydrophobic by Span 80, resulting in the formation of w/o emulsions. The long-term stability of the emulsions was also compared. Emulsions stabilized by Span 80 alone completely separate into two bulk phases of oil and water after 3 months. However, emulsion stability is greatly enhanced with the addition of LDH or Laponite particles. This synergism was accounted for by an increase of the dilational viscoelasticity modulus of the oil-water interface after particles were added to the aqueous phase. This increase indicates that the gel-like particle layer stays at the oil-water interface and resists emulsion coalescence. Scanning electron microscope (SEM) images display the presence of a firm layer surrounding the emulsion droplets and a three-dimensional particle network which extends into the bulk phase aiding emulsion stability